URBAN CYCLING AS AN INDICATOR OF SOCIO-ECONOMIC INNOVATION AND SUSTAINABLE TRANSPORT - Kwiatkowski, Michał Adam (Quaestiones Geographicae, 2018)
Environmental pollution in cities is an increasingly popular issue tackled in research. One of the elements with a significant impact on the state of urban ecosystems is transport with its pressure on individual components of the environment. Sustainable urban transport is gaining prominence as a postulate expressed in cities’ strategic documents, constituting an element alleviating the negative effects of anthropopressure. In the light of the need to introduce innovative solutions for clean forms of transport, numerous papers indicate the bicycle as an answer to some of those problems. The article presents a review of literature referring to the socio-economic aspects of using the bicycle in cities as a means of transport for daily commuting. The analysis is based on publications on cyclist safety in road traffic, the perception of the bicycle as a means of transport in cities, and the introduction of innovative solutions, such as bicycle-sharing systems.